Pembangunan Pemukiman Orang Asli Papua Dalam Perspektif Antropologi Papua di Kota Sorong - Imanuel Tenau (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Domus Propria Domus Optima means that one's own home is always the best home. Home, this is the first door to enter the gate of life activities. Indigenous Papuans provide a gateway to home, neighbor and nature that presents itself to others. Settlement is the first awareness of humans to relate to others (the other). The other is a description of esse in its totality to create an encounter with nature. Settlement displays the facticity of the esse, which places me and the other in temporality. Indigenous Papuans and their settlements illustrate human life that has often been discussed by everyone so far. The discussion that always arises is the difficulty of accepting the modernity of existing settlements. Differences in culture, ethnicity, character, religion prevent indigenous Papuans from feeling at home. Indigenous Papuans feel at home with God, others and nature in their settlements. At home shows the nature of indigenous Papuans who have two dimensions, namely personal and social dimensions. The personal dimension expresses the quality side in him that has uniqueness so that it distinguishes him from others. Here the indigenous Papuan is able to determine himself and all his actions. Likewise, the social dimension makes indigenous Papuans unable to live alone. He can always meet with God, others and nature. This is where indigenous Papuans realize themselves as true human beings. This condition makes indigenous Papuans act uniquely as humans.